The Role of Magnetic Resonance Imaging in Athletic Pubalgia and Core Muscle Injury. Issue 4 (August 2015) - Coker, Dana J.; Zoga, Adam C.
<x xml:space="preserve">Abstract</x> Abstract Magnetic resonance imaging (MRI) has become the standard of care imaging modality for a difficult, often misunderstood spectrum of musculoskeletal injury termed athletic pubalgia or core muscle injury. Armed with a dedicated noncontrast athletic pubalgia protocol and a late model phased array receiver coil, the musculoskeletal imager can play a great role in effective diagnosis and treatment planning for lesions, including osteitis pubis, midline pubic plate lesions, and rectus abdominis/adductor aponeurosis injury. Beyond these established patterns of MRI findings, there are many confounders and contributing pathologies about the pelvis in patients with activity related groin pain, including internal and periarticular derangements of the hip. The MRI is ideally suited to delineate the extent of expected injury and to identify the unexpected visceral and musculoskeletal lesions.